On the Possibility of Tidal Formation of Binary Planets Around Ordinary Stars - Podsiadlowski, P; Rappaport, S; Fregeau, J; Mardling, R (2010)
The planet formation process and subsequent planet migration may lead to configurations resulting in strong dynamical interactions among the various planets. Well-studied possible outcomes include collisions between planets, scattering events that eject one or more of the planets, and a collision of one or more of the planets with the parent star. In this work we consider one other possibility that has seemingly been overlooked in the various scattering calculations presented in the literature: the tidal capture of two planets which leads to the formation of a binary planet (or binary brown dwarf) in orbit about the parent star. We carry out extensive numerical simulations of such dynamical and tidal interactions to explore the parameter space for the formation of such binary planets. We show that tidal formation of binary planets is possible for typical planet masses and distances from the host star. The detection (or lack thereof) of planet-planet binaries can thus be used to constrain the properties of planetary systems, including their mutual spacing during formation, and the fraction of close planets in very eccentric orbits which are believed to form by a closely related process.